Effects of Forest Area, Environmental Patents And Financial Progress on Carbon Emissions in Azerbaijan - Korkut Pata Ugur; Karlilar Pata Selin (BIO Web of Conferences)
Decarbonization is at the top of the global agenda, with many countries setting net zero emissions sustainable development goals. Azerbaijan is a country that has managed to significantly reduce its carbon emissions in recent years, and analyzing the determinants of carbon emissions is important for Azerbaijan to continue this success. In this context, the study aims to examine the impact of forest area, financial development, environmental patents and economic growth on carbon emissions according to the Environmental Kuznets Curve (EKC) hypothesis for Azerbaijan over the period 1992-2021. To this end, the study tests the validity of the EKC using the ARDL approach. In addition, the study shows that financial development increases environmental problems, environmental patents have no effect on carbon emissions, and forest area is a critical factor for decarbonization. In light of these results, the government of Azerbaijan should expand its policies to promote afforestation in order to achieve a zero-carbon economy.